Hubungan Harga CPO, Nilai Kurs, dan IHSG selama Era Labelisasi Palm Oil Free - Hary Saputra Sundoro (Universitas Bina Sarana Informatika, 2022)
Indonesia is the largest country in producing CPO of the world. CPO price should have relationship with Indonesia economy on to exchange rate and capital market. Moreover, Palm Oil Free policy has been released which is prohibit to consume CPO. This will certainly have an impact on the price of CPO which will later have a relationship with the exchange rate and the JCI.The research aims to determine the relationship between CPO prices, exchange rates and JCI during the Palm Oil Free period. The research method is VECM. The period is conducted during from January 2017 to June 2021. The result of the research is the CPO price and the exchange rate have a positive relationship. Then, JCI and the CPO price have a negative relationship and the relationship between the exchange rate and the JCI is positive during the Palm Oil Free era. The implication shows that the government must be able to control the price of CPO considering that this variable can be related to other macroeconomic fundamentals such as the exchange rate and capital market index. Keywords: CPO Price; Exchange Rate; JCI